Short-Term Oral Quercetin Supplementation Improves Post-exercise Insulin Sensitivity, Antioxidant Capacity and Enhances Subsequent Cycling Time to Exhaustion in Healthy Adults: A Pilot Study - Tsao, Jung-Piao; Bernard, Jeffrey R.; Hsu, Hsiu-Chen; Hsu, Chin-Lin; Liao, Su-Fen; Cheng, I-Shiung (Frontiers in Nutrition, 2022)
Aim: Quercetin has been reported to have antioxidant and anti-inflammatory properties on health promotion in human studies. The main purpose of this study was to investigate the effect of short-term oral quercetin supplementation on post-exercise whole-body energy metabolism. This study also aimed to determine the effects of supplementation on oxygen stress, inflammation, muscle damage, and high-intensity cycling exercise performance. Method: Twelve healthy participants, physically active students, were recruited to perform a randomized, single-blind crossover study. All subjects completed 7-days of quercetin (quercetin:1,000 mg per day for 7-days) and placebo supplementation in a randomized order. Supplement/placebo was combined with exercise consisting of 70% V̇O2max cycling for 60-minutes, followed by 3-hours of recovery, then a subsequent single bout of cycling exercise with 75% V̇O2max to exhaustion. Time to exhaustion, indicators of muscle damage, as well as blood and gaseous parameters relating to energy metabolism, oxidative stress, inflammatory response, respectively, were determined. Results: The results showed that 7-day quercetin supplementation significantly attenuated the post-exercise glucose-induced insulin response, increased TAC and SOD activities, and mitigated MDA levels during the recovery period (p < 0.05). While subsequent 75% V̇O2max cycling performance was significantly improved after quercetin treatment and accompanied by lower responses of IL-6 and creatine kinase at 24-hours. However, it’s noted that there were no significant responses in glucose, respiratory exchange rate, TNF-α, myoglobin, and high sensitivity C-reactive protein between quercetin and placebo trials. Conclusion: Our findings concluded that 7-day oral quercetin supplementation enhances high-intensity cycling time to exhaustion, which may be due in part to the increase in whole-body insulin-stimulated glucose uptake and attenuation of exercise-induced oxygen stress and pro-inflammation. Therefore, quercetin may be considered an effective ergogenic aid for enhancing high-intensity cycling performance among young adults.